Analysis of Comprehensive Denmark Country Environmental Policy Success in 2020-2022 (Denmark, from a Many Greenhouses Gas Emission Country to a Green Country That Protects Its Environment) - Tessalonica Manuputty; Agung Yudhistira Nugroho (Budapest International Research and Critics University, 2022)
Environmental issues have become the attention of many world countries, especially member countries of the European Union, where the European Union has policies and targets for its region. This agreement binds 27 European countries, making these policies the region's primary law. Member countries, one of which is Denmark, will be discussed in this study. Unlike other European countries, Denmark has a long-term and is committed to protecting the environment. This study aims to analyze Denmark's environmental policy in overcoming environmental damage and its commitment to using renewable resources. It can be seen from the available data that Denmark occupied country number 1 for three years, namely 2020-2022, as the one with the highest score in protecting the environment, of course with active, comprehensive policies and high public awareness to protect the environment.